2018
DOI: 10.3346/jkms.2018.33.e183
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Safety Profiles between Non-operating Room Anesthesia and Operating Room Anesthesia: a Study of 199,764 Cases at a Korean Tertiary Hospital

Abstract: BackgroundDespite expanding demands for non-operating room anesthesia (NORA) worldwide, studies in this field are scarce. We compared the overall characteristics and the nature of deaths occurring within 48 hours after surgery between NORA and operating room anesthesia (ORA) cases at a Korean tertiary hospital.MethodsWe retrospectively analyzed the medical records of patients who underwent surgical procedures under anesthesia services in and outside the operating room from January 2013 to November 2017. All of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Treatments requiring general anaesthesia, besides surgical operation, include cardiovascular catheterisation such as ablation, stent graft interpolation, endovascular treatment, radiological embolisation, gamma knife, and proton beam therapy (PBT) 2 . Performing general anaesthesia outside the operating room raises safety and quality issues due to the limited availability of equipment and anaesthesiologists, who might not be available in case of an emergency 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Treatments requiring general anaesthesia, besides surgical operation, include cardiovascular catheterisation such as ablation, stent graft interpolation, endovascular treatment, radiological embolisation, gamma knife, and proton beam therapy (PBT) 2 . Performing general anaesthesia outside the operating room raises safety and quality issues due to the limited availability of equipment and anaesthesiologists, who might not be available in case of an emergency 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Claims for adverse respiratory events, including hypoventilation, aspiration and difficult intubation, occurred with at least twice the frequency [10]. Poor outcomes were often associated with suboptimal care and nonadherence to safe practice [10,11].…”
Section: Nonoperating Room Anaesthesia Adverse Event Analysismentioning
confidence: 99%
“…Deepening sedation by nonanaesthesiologists can rapidly lead to general anaesthesia [ 21 , 22 ] (Table 2 ) and training may not always be adequate for the task. A review of the Korean Society of Anesthesiology database from 2009 to 2014 revealed avoidable complications in 34 of 39 cases, 92.4% involving nonanaesthesiologists [ 11 ].…”
Section: Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…catheterization such as ablation, stent graft interpolation, endovascular treatment, radiological embolization, gamma knife and proton beam therapy (PBT) (2). Performing general anesthesia outside the operating room raises safety and quality issues due to the limited availability of equipment and anesthesiologists, who might not be available in case of an emergency (3,4).…”
Section: Treatments Requiring General Anesthesia Besides Surgical Opementioning
confidence: 99%